[PP.19.12] ASSOCIATION OF ISOLATED MORNING HYPERTENSION WITH ARTERIAL MEASURES IN UNTREATED CHINESE PATIENTS. (September 2017) - Guo, Q.; Cheng, Y.B.; Zhang, D.Y.; Huang, Q.F.; Sheng, C.S.; Wang, J.G.; Li, Y.
Abstract : Objective: Morning hypertension was suggested to be closely associated with target organ damage and cardiovascular events. However, the independent contribution of morning hypertension to cardiovascular damage remains controversial. The purpose of our study was to investigate the association of isolated morning hypertension with measures of arterial stiffness and microalbuminuria in an untreated outpatient cohort. Design and method: We recruited consecutive outpatients who was suspected of having hypertension but not taking antihypertensive drugs for at least 2 weeks and referred to our hypertension clinic from November 2010 to June 2015. Home BP was self-measured with the Omron 7051 monitors for 7 days. Hypertension was defined as a mean home BP of at least 135/85 mmHg either in the morning or in the evening. We assessed carotid-femoral pulse wave velocity (cfPWV) and central augmentation index (cAIx) with the SphygmoCor system as measures of arterial stiffness, and the morning urinary albumin/creatinine ratio (ACR) as measures of microalbuminuria. Results: In the 1537 untreated outpatients (mean age, 51.0 years; women, 51.9%), 200 (13.0%) had isolated morning hypertension. Patients with isolated morning hypertension compared to normotensive subjects had faster cfPWV (8.1 vs 7.5 cm/s, P < 0.001), increased urinary ACR (0.76 vs 0.65 mg/mmol, P = 0.049), but similar cAIx (26.7 vs 25.3%, P = 0.14). After adjustment for age, sex, body height and weight, heart rate, current smoking and alcohol intake, serum total cholesterol and fasting glucose, the between-group difference in cfPWV (8.0 vs 7.5 cm/s, P < 0.001), cAIx (25.8 vs 23.5%, P < 0.001) and ACR (0.72 vs 0.62, P = 0.037) were statistically significant. In continuous analysis, home morning systolic BP was significantly (P < 0.001) associated with cfPWV and ACR after adjustment with aforementioned variables and evening SBP. In addition, for cfPWV and ACR, morning systolic BP explains the greatest part of the variations in the model. Conclusions: The prevalence of isolated morning hypertension is 13% in our untreated Chinese outpatients. Isolated morning hypertension is associated with arterial stiffness and increased wave reflections in untreated Chinese patients. Home morning BP was independently associated with arterial damage.